STUDYING FUNGICIDAL PROPERTIES OF MINERALIZED STRATUM WATER ON MILLET AREAS - Pysarenko, P. V.; Samoilik, M. S.; Dychenko, O. Yu.; Ts’ova Yu. А.; Bezsonova V. А.; Liskonog К. М. (Scientific Progress & Innovations, 2021)
It has been pointed out in the paper that scientific substantiation and development of measures of using mineralized stratum water for fungicidal plant protection are topical, which corresponds to the requirements of environmentally friendly resource saving technologies of crop cultivation. That is why the aim of this re-search was studying fungicidal properties of mineralized stratum water on millet areas. As a result of con-ducted experiments it has been established that mineralized stratum water in any of its concentrations effec-tively inhibits spore germination of millet loose smut causative agents. Practically in all solutions except 15 % (89.7 %), 20 % (70.5 %) and 25% (85.4 %) of mineralized stratum water, this indicator was not less than 90%. The concentrations of 100 % and 60% of mineralized stratum water turned out to be the most ef-fective. On these variants, 98.3% and 98.8 % inhibition of germinating the spores of millet loose smut path-ogens was obtained. It has been established that applying the mixture of different mineralized stratum water (MSW) concentrations and Sumy-8 disinfectant increased plant germination to 19 and 28 %. The smallest number of millet plants was found on the plots where Sumy-8 disinfectant was used at the decreased rate of 1 kg/t – 19.6 pcs. While applying Sumy-8 preparation in the mixture of 50 % and 25 % MSW concentration, the number of millet plants on the plots was 4 and 5 pieces more, respectively. As a result of the experiments, it has been determined that millet seeds treatment with MSW somehow decreases plant infestation with loose smut. The most inhibition was observed in the variant of applying 25 % MSW and 25 % MSW + Sumy-8 (1 kg/t). The number of infected plants in these variants made 0.3, on the average. 50 % MSW concentration affected millet tillering capacity most of all, which increased productive tillering capacity to 1.5, and 25% MSW concentration – to 1.4. Besides productive tillering capacity, the application of 50% MSW affected thousand-seed weight. As a result of conducting several series of laboratory experiments to study the impact of MSW on germination of fungi thelyo-spores, which are causative agents of wheat covered smut and millet loose smut, considerable fungus-toxic effect was found. Mineralized stratum water disturbed the process of spore germination in a large concentration range from 15 to 100 %. Moreover, inhibition percentage of thelyo-spore germination increased from 90 to 98 %. Thus, it can be maintained that MSW even being dis-solved with water in 1:7 ratio has fungus-toxic properties at the same level or even higher than similar commercial fungicides.